La Iglesia católica en América Latina a la hora del papa Francisco - Rodolfo de Roux (Caravelle)
In Latin-America the developement of religious pluralism, the consolidation of Protestant Pentecostalism Churches, the increase of society’s secularisation and the weakening of catholic hegemony is being confirmed. Facing these challenges, the Catholic Church answered since the 1980s with an institutional strenghtening, a larger power centralisation, a control over theological thinking but also by quelling dissident or alternative tendencies. Within that movement of “returning to the big discipline”, the recent election of pope Francis has blown the winds of the opening and renovation, but the challenges that the Church has to take up, inside as well as outside, are huge.